Evaluation of COVID-19 RT-qPCR Test in Multi sample Pools. (2nd May 2020) - Yelin, Idan; Aharony, Noga; Tamar, Einat Shaer; Argoetti, Amir; Messer, Esther; Berenbaum, Dina; Shafran, Einat; Kuzli, Areen; Gandali, Nagham; Shkedi, Omer; Hashimshony, Tamar; Mandel-Gutfreund, Yael; et al.
Abstract: Background: The recent emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to a current pandemic of unprecedented scale. Although diagnostic tests are fundamental to the ability to detect and respond, overwhelmed healthcare systems are already experiencing shortages of reagents associated with this test, calling for a lean immediately applicable protocol. Methods: RNA extracts of positive samples were tested for the presence of SARS-CoV-2 using reverse transcription quantitative polymerase chain reaction, alone or in pools of different sizes (2-, 4-, 8-, 16-, 32-, and 64-sample pools) with negative samples. Transport media of additional 3 positive samples were also tested when mixed with transport media of negative samples in pools of 8. Results: A single positive sample can be detected in pools of up to 32 samples, using the standard kits and protocols, with an estimated false negative rate of 10%. Detection of positive samples diluted in even up to 64 samples may also be attainable, although this may require additional amplification cycles. Single positive samples can be detected when pooling either after or prior to RNA extraction. Conclusions: As it uses the standard protocols, reagents, and equipment, this pooling method can be applied immediately in current clinical testing laboratories. We hope that such implementation of a pool test for coronavirus disease 2019 would allow expanding current screening capacities, thereby enabling the expansion of detection in the community, as well as in close organic groups, such as hospital departments, army units, or factory shifts. Abstract : A single positive sample can be detected in pools of up to 32 using the standard COVID-19 RT-qPCR test. Such pooling methodology, immediately applicable using current equipment and reagents, will allow routine population surveillance while conserving scarce resources.